Alienação artística: Marcuse e a ambivalência política da arte - Silveira, Luís Gustavo Guadalupe (2009)
The ambivalent political character of art, presented by Marcuse in texts that embrace five decades of intellectual production, is the subject of our study. The main goal is make explicit how Marcuse grounds this ambivalence, which assigns an affirmative and a negative potential to the aesthetic dimension. This investigation seeks presenting the philosopher s description of the political aspect of art; explicating the conciliatory function of art in formation and maintenance of the bourgeois society and, later, of the one-dimensional society; investigating whether there is a change on his appreciation about affirmative and negative art through his works or not, and, if it is the case, explicating his arguments to those changes. Therefore, we have analyzed texts from 1937 to interviews conceded by Marcuse in 1979. We also debated with different interpreters of his thought to better understand his work. We started from five hypothesis: 1) political (negative or affirmative) potential of art is based on it s alienating aspect and it s related to the subjectivity valorization searched by Marcuse; 2) the political character of art substantially depends on the historical context; 3) there is no significant variation in Marcuse s reflections about political character of art between the 1930s and the 1970s. There is a (small) variation on his appraisal of the subversive potential of certain artistic movements along the 20th century; 4) another variable is his emphasis on revolutionary, emancipatory, reconciliatory, conformist or positives aspects of art through his works. According to our conclusion, the entire five hypotheses were confirmed, despite the lack of consensus and the commentators disagreement about the variations and nature of Marcuse s reflections on art.